2018
DOI: 10.19044/esj.2018.v14n33p70
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation du comportement trophique de Aedes aegypti dans la ville de cotonou au sud du Bénin

Abstract: In order to evaluate the trophic behavior of Aedes aegypti in the city of Cotonou, southern Benin, a cross-sectional study was conducted in urban and periurban neighborhoods from April 2016 to August 2017 to collect Ae. Aegypti populations. To achieve this goal, day and night collections, twice a month for one year were done where Ae. Aegypti populations were caught by Human Landing Catch and BG-Sentinel traps. 3,892 Aedes caught by different methods showed that Ae. Aegypti and Ae. circumluteolus are more abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…The enormous quantities of insecticides of the same class used in agriculture could be at the origin of this overproduction of oxidases. The glutathione-S-transferase activity observed in our vector populations confirms the strong resistance to DDT observed by Yadouleton et al [ 2 ] in Ae. aegypti in Benin.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The enormous quantities of insecticides of the same class used in agriculture could be at the origin of this overproduction of oxidases. The glutathione-S-transferase activity observed in our vector populations confirms the strong resistance to DDT observed by Yadouleton et al [ 2 ] in Ae. aegypti in Benin.…”
Section: Discussionsupporting
confidence: 91%
“…Aedes aegypti is the main indigenous vector of arboviruses in Africa [ 1 ]. In Benin, it remains abundant in both the south and the north parts of the country [ 2 , 3 ]. Recent studies have reported the presence of Aedes albopictus , a vector native to Asia, in Southern Benin [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, there are no reports on current outbreaks of arboviruses although the DENV seems to be endemic with two reported human cases (56,57) and CHIKV seem to circulate as suggested by a couple of studies (54,55). The low numbers of arbovirus cases in Benin might be due to under-diagnosed or under-reported cases, as DENV for example has similar symptoms to malaria (27). In contrast to Gabon, mosquito surveillance studies revealed the dominance of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…vitattus and Ae. luteocephalus was observed in Gabon, even though these species of mosquito are present in West Africa (26)(27)(28)(34)(35)(36)(37). This absence might be attributed to the extensive forested areas in Gabon, where over 88% of its total surface is covered by rainforests, making it one of the most forested countries globally.…”
Section: Mosquito Vectors Of Arbovirusesmentioning
confidence: 99%
“…The previous studies conducted in much smaller areas revealed the presence of four Aedes species in Cotonou [ 47 ] and three in Abomey-Calavi [ 21 ]. In the present study, Ae.…”
Section: Discussionmentioning
confidence: 99%